2019
DOI: 10.1021/acs.jpca.9b08974
|View full text |Cite
|
Sign up to set email alerts
|

Electron Attachment to DNA Base Pairs: An Interplay of Dipole- and Valence-Bound States

Abstract: We have investigated the electron-attached states in Watson−Crick guanine−cytosine and adenine− thymine base pairs using the highly accurate equation-ofmotion coupled-cluster (EOM-CC) method and extended basis sets. Both base pairs have two bound anionic states. The dipole-bound state is stable even at the neutral geometry, but the valence-bound state is only adiabatically bound. The initial electron attachment results in the formation of a dipole-bound state that acts as a doorway to the valence-bound anionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…Here,W is the electron coupling matrix element between the two electronic states, ΔG0 is the free energy difference between the dipole bound and valence bound states and Er is the reorganization energy of the valence bound state. The calculated rate coefficient for the transfer of electron is 1.74×10 12 s −1 at room temperature, which almost an order of magnitude more than that observed for the bare GC base‐pair (4.07×10 11 s −1 ). It shows that even a single water molecule can significantly increase the rate of transition of the electron from the initial dipole‐bound to the valence bound state by providing extra stability to the anion through hydrogen bonding.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Here,W is the electron coupling matrix element between the two electronic states, ΔG0 is the free energy difference between the dipole bound and valence bound states and Er is the reorganization energy of the valence bound state. The calculated rate coefficient for the transfer of electron is 1.74×10 12 s −1 at room temperature, which almost an order of magnitude more than that observed for the bare GC base‐pair (4.07×10 11 s −1 ). It shows that even a single water molecule can significantly increase the rate of transition of the electron from the initial dipole‐bound to the valence bound state by providing extra stability to the anion through hydrogen bonding.…”
Section: Resultsmentioning
confidence: 66%
“…The entire system was treated using a DFT based method, and the additional electron was found to be delocalized over both the bases. This is in stark contrast to the situation in gas‐phase where the additional electron in guanine−cytosine (GC) anion is solely localized over the cytosine. The previous microsolvation and PCM‐based studies on GC base‐pair have also reported the extra electron to be localized on cytosine.…”
Section: Introductionmentioning
confidence: 80%
“…Electron attachment to nucleobases is a crucial step in the secondary radiation damage [115][116][117][118] pathway of genetic materials. However, accurate wave-function based simulation of the electron attachment to genetic material is restricted at most to the base-pairs owing to the high computation cost of the calculations 119,120 .…”
Section: Dna Model Systemmentioning
confidence: 99%
“…The EA-EOM-DLPNO-CCSD calculations are then performed using aug-cc-pVTZ basis set with an additional 5s5p4d diffuse function added to the positive end of the dipole. The electron attachment to GC base-pair leads to two bound anionic states 120 . The first one is a dipole bound state which is vertically bound.…”
Section: Adiabatic Electron Affinity Of Gc Base Pairmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The DBS is known to play an important role as the doorway state to the stable valence anion formation. [9][10][11][12][13] Namely, as the slow electron approaches the neutral molecule or radical, the incoming electron is captured in the form of the Feshbach resonances by the long-range attractive interaction potential, and it is followed by the subsequent coupling and/or relaxation into the more stable anion species. 14,15 Detailed pictures of the whole processes of the electron-capturing, coupling, and relaxation are thus quite essential for the thorough understanding of the anion chemistry as well as the entry/exit dynamics of the redox reactions.…”
mentioning
confidence: 99%